A polymer solid-state electrolyte of a lithiumated thermoplastic polyurethane elastomer
Patent Information
- Application Number
- CN202310533979.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-11
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-05-11
AI Technical Summary
但聚合物的柔性也面临在锂离子电池循环过程中,被锂枝晶刺穿的风险,造成锂离子电池短路并带来安全风险,而当前市面上常用的聚合物电解质膜较差的机械强度则难以解决此问题
[0021] This invention utilizes room-temperature ionic liquid small molecules as functional additives in lithium-ion TPU-based polymer solid electrolytes. Through the ionic interaction between specific functional groups in the functional additive and acid radicals, lithium-ion dissociation is promoted, increasing lithium-ion concentration and enhancing the mobility of polymer chains, thus improving lithium-ion conduction. The lithium-ion TPU polymer chain itself comprises hard and soft segments. The hard segments provide high mechanical strength, while the soft segments provide lithium-ion coordination sites. Grafting anionic acid radicals forms an ionic spatial conduction network, resulting in a polymer solid electrolyte membrane that possesses both excellent mechanical properties and ionic conductivity, high tensile strength, and promotes stable lithium-ion deposition/stripping. This method of preparing a solid electrolyte membrane overcomes the adverse effects of excessively strong interactions between acid radicals and lithium ions, improves ionic conductivity, and maintains the good mechanical properties of the lithium-ion TPU substrate material, enabling large-scale processing and application in all-solid-state lithium-ion batteries.
Smart Images

Figure CN116505067B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a polymer solid electrolyte of lithium-ionized thermoplastic polyurethane elastomer, belonging to the field of polymer solid electrolyte preparation technology. Background Technology
[0002] Currently, global environmental issues and China's energy transition policies have led to a surge in market demand for lithium-ion batteries. However, most lithium-ion battery electrolytes on the market are organic. While lithium-ion batteries have high energy density, the flammability of these electrolytes poses serious safety risks. Therefore, to address the safety concerns of lithium-ion batteries, replacing flammable organic electrolytes with non-flammable solid electrolytes would significantly improve battery safety. Currently, the most widely researched electrolytes are inorganic ceramics, polymer electrolytes, and inorganic-organic hybrid electrolytes. Polymer electrolytes can solve the problem of excessive electrolyte-electrode interface impedance in inorganic ceramic electrolytes, and through appropriate structural design, they can also achieve considerable ionic conductivity, thus becoming a focus of current research and development. Although polymer solid electrolytes (SSEs) possess excellent interfacial properties and safety, improving battery coulombic efficiency and cycle life, and have a wide electrochemical stability window, they can be matched with high-voltage cathode materials to increase battery energy density. However, the flexibility of polymers also poses a risk of being punctured by lithium dendrites during lithium-ion battery cycling, causing short circuits and posing safety risks. The poor mechanical strength of currently used polymer electrolyte films makes this problem difficult to solve. On the other hand, polymer solid electrolytes prepared based on the traditional PEO plus lithium salt system struggle to achieve a conductivity of 10. -4 S cm -1 The current solid-state electrolytes (SSEs) do not meet the basic requirements for practical use of solid-state lithium-ion batteries. While PEO lithium salt systems with additives achieve good ionic conductivity, they often suffer from a decline in mechanical properties. In short, existing solid-state electrolytes often struggle to balance ionic conductivity and mechanical properties. Summary of the Invention
[0003] This invention provides a lithium-ionized thermoplastic polyurethane elastomer polymer solid electrolyte, which can effectively solve the above-mentioned problems.
[0004] This invention is implemented as follows:
[0005] A method for preparing a polymer solid electrolyte of lithium-ionized thermoplastic polyurethane elastomer includes the following steps:
[0006] S1, extend the polyurethane chain to obtain extended polyurethane elastomer, and then lithilate the extended polyurethane elastomer to obtain lithilated TPU.
[0007] S2, Lithium-ionized TPU and lithium salt are dissolved in an organic solvent, functional additives are added, and the mixture is heated and stirred for a period of time to form a composite solution;
[0008] S3, the composite solution is poured onto a smooth substrate, the solvent evaporates, and the substrate is left to age for a period of time to form a film;
[0009] S4, the film is peeled off, hot-pressed, and cut into pieces to form the polymer solid electrolyte of the lithium-ionized thermoplastic polyurethane elastomer.
[0010] As a further improvement, the step of obtaining extended polyurethane elastomer by chain extension of polyurethane is as follows: a certain mass of ether-oxygen oligomer is weighed into a container, placed in an oil bath under an inert atmosphere, a certain amount of MDI is dissolved in anhydrous CHCl3, and added to the ether-oxygen oligomer with stirring. After heating and reacting for several hours, the mixture is cooled to obtain a prepolymer. The chain extender is dissolved in an anhydrous organic solvent and added to the prepolymer. The temperature is gradually raised to about 70-100°C, and the mixture is stirred and reacted for a period of time to obtain the chain-extended polyurethane elastomer.
[0011] As a further improvement, the ether-oxygen segment prepolymer includes one or more of polyethylene oxide, polyethylene glycol, and polytetrahydrofuran.
[0012] As a further improvement, the chain extender includes one or more of polyethylene glycol, polybutylene glycol, and polyglycerol.
[0013] As a further improvement, the step of lithiating the extended polyurethane elastomer to obtain lithium-ion TPU is as follows: the extended polyurethane elastomer is added to an organic solvent to prepare a TPU solution, the TPU solution is cooled to about -20 to -5°C, NaH is added, and the mixture is stirred evenly. The temperature is then raised to -6°C to 5°C and reacted for a period of time. Then, PS is added at a certain stoichiometric ratio at -10°C, and after stirring and mixing, the mixture is reacted for a period of time and then the temperature is raised. After cooling, excess NaH is quenched with a quencher to obtain sodium-ionized TPU polymer. Finally, Na ions are replaced with Li ions by ion exchange to obtain lithium-ionized TPU.
[0014] As a further improvement, the mass ratio of the lithium-ionized TPU, functional additives, and lithium salt is 30-50 wt%, 30-40 wt%, and 10-30 wt%, respectively.
[0015] As a further improvement, the functional additives are the following room-temperature ionic liquids: [BMIM]TFSI, [EMIM]FSI, [BMIM]OTF, and [PY]. 14 One or more of the following: OTF.
[0016] As a further improvement, the smooth substrate includes one of silicon wafers, steel sheets, glass sheets, and PTFE sheets, and is made of a thermally conductive and inert material.
[0017] As a further improvement, the degree of lithiation of the lithium-ionized TPU is 30-100%.
[0018] As a further improvement, the hot pressing temperature is 30°C to 80°C.
[0019] A polymer solid electrolyte of lithium-ionized thermoplastic polyurethane elastomer prepared by the above method.
[0020] The beneficial effects of this invention are:
[0021] This invention utilizes room-temperature ionic liquid small molecules as functional additives in lithium-ion TPU-based polymer solid electrolytes. Through the ionic interaction between specific functional groups in the functional additive and acid radicals, lithium-ion dissociation is promoted, increasing lithium-ion concentration and enhancing the mobility of polymer chains, thus improving lithium-ion conduction. The lithium-ion TPU polymer chain itself comprises hard and soft segments. The hard segments provide high mechanical strength, while the soft segments provide lithium-ion coordination sites. Grafting anionic acid radicals forms an ionic spatial conduction network, resulting in a polymer solid electrolyte membrane that possesses both excellent mechanical properties and ionic conductivity, high tensile strength, and promotes stable lithium-ion deposition / stripping. This method of preparing a solid electrolyte membrane overcomes the adverse effects of excessively strong interactions between acid radicals and lithium ions, improves ionic conductivity, and maintains the good mechanical properties of the lithium-ion TPU substrate material, enabling large-scale processing and application in all-solid-state lithium-ion batteries.
[0022] The present invention only requires solution casting to prepare electrolyte membranes, without the need for electrospinning, a traditional preparation method. The preparation method is simple and consumes little energy. Attached Figure Description
[0023] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained from these drawings without creative effort.
[0024] Figure 1 The temperature-conductivity curve of a polymer solid electrolyte based on a novel lithium-ionized TPU provided in Embodiment 1 of the present invention.
[0025] Figure 2 The all-solid-state lithium-ion battery assembled using a novel lithium-ion TPU-based polymer solid electrolyte provided in Example 1 of this invention was tested at 0.01 mA / cm. 2 0.02mA / cm 20.05mA / cm 2 0.1mA / cm 2 0.2mA / cm 2 0.1mA / cm 2 Cyclic-specific capacity curves at current densities.
[0026] Figure 3 To utilize the novel lithium-ionized TPU-based polymer solid electrolyte provided in Example 1 of this invention, at 0.01 mA / cm 2 0.02mA / cm 2 0.05mA / cm 2 0.1mA / cm 2 0.2mA / cm 2 0.4mA / cm 2 0.2mA / cm 2 Cyclic stability of Li||Li symmetric cells at current density. Detailed Implementation
[0027] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to represent selected embodiments of the invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0028] This invention provides a method for preparing a polymer solid electrolyte of lithium-ionized thermoplastic polyurethane elastomer, comprising the following steps:
[0029] S1, extend the polyurethane chain to obtain extended polyurethane elastomer, and then lithilate the extended polyurethane elastomer to obtain lithilated TPU.
[0030] S2, Lithium-ionized TPU and lithium salt are dissolved in an organic solvent, functional additives are added, and the mixture is heated and stirred for a period of time to form a composite solution;
[0031] S3. The composite solution is poured onto a smooth substrate. After the solvent evaporates, it is allowed to stand and age for a period of time to form a film. The film is then heated to evaporate most of the solvent and then placed in a vacuum oven to dry the remaining solvent.
[0032] S4, the film is peeled off, hot-pressed, and cut into pieces to form the polymer solid electrolyte of the lithium-ionized thermoplastic polyurethane elastomer.
[0033] The membrane thickness is approximately 30–200 μm. Membranes of this thickness exhibit the best processing performance during battery assembly and also demonstrate the best overall performance within the battery. The above operations are carried out in a glove box or drying chamber (humidity less than 0.1%).
[0034] As a further improvement, the step of obtaining extended polyurethane elastomer by chain extension of polyurethane is as follows: a certain mass of ether-oxygen chain oligomer is weighed into a container, placed in an oil bath under an inert atmosphere, a certain amount of diphenylmethane diisocyanate (MDI) is dissolved in anhydrous CHCl3, and added to the ether-oxygen chain oligomer with stirring. After heating and reacting for several hours, the mixture is cooled to obtain a prepolymer. The chain extender is dissolved in anhydrous organic solvent and added to the prepolymer. The temperature is gradually raised to 70-100°C, and the mixture is stirred and reacted for a period of time to obtain the chain-extended polyurethane elastomer.
[0035] As a further improvement, the ether-oxygen segment prepolymer includes one or more of polyethylene oxide, polyethylene glycol, and polytetrahydrofuran.
[0036] As a further improvement, the chain extender includes one or more of polyethylene glycol, polybutylene glycol, and polyglycerol.
[0037] As a further improvement, the molar ratio of the ether oxide oligomer, diphenylmethane diisocyanate, and chain extender is 4-2:1:1-3, and more preferably 4:1:1, 4:1:2, 4:1:3, 2:1:1, 2:1:2, or 2:1:3.
[0038] As a further improvement, the organic solvent includes one or more of NMP, CHCl3, acetone, methanol, ethanol, glycerol, acetonitrile, DMF, and THF.
[0039] As a further improvement, the step of lithiating the extended polyurethane elastomer to obtain lithium-ion TPU is as follows: the extended polyurethane elastomer is added to an organic solvent to prepare a TPU solution, the TPU solution is cooled to about -20 to -5°C, NaH is added, and the mixture is mixed evenly. The temperature is then raised to -6°C to 5°C and reacted for a period of time. Then, propane sulpholactone (PS) is added at a certain stoichiometric ratio at -10°C, and after stirring and mixing, the mixture is reacted for a period of time and then the temperature is raised. After cooling, excess NaH is quenched with a quencher to obtain sodium-ionized TPU polymer. Finally, Na ions are replaced with Li ions by ion exchange to obtain lithium-ionized TPU.
[0040] As a further improvement, the quencher is one or more of methanol, ethanol, glycerol, acetonitrile, acetone, and tetrahydrofuran.
[0041] As a further improvement, the degree of lithiation of the lithiated TPU is 30-100%. The lithiation can be adjusted by the stoichiometric ratio of chain-extended polyurethane elastomer, propane sulpholactone (PS), and NaH.
[0042] As a further improvement, the mass ratio of the lithium-ionized TPU, functional additives, and lithium salt is 30-50 wt%, 30-40 wt%, and 10-30 wt%, respectively. Only at this feed ratio can a homogeneous polymer electrolyte film with good overall performance be prepared; otherwise, partial breakdown or film hardening and brittleness may occur.
[0043] As a further improvement, the functional additives are the following room-temperature ionic liquids: [BMIM]TFSI, [EMIM]FSI, [BMIM]OTF, and [PY]. 14 One or more of the following OTFs, preferably [BMIM]TFSI.
[0044] As a further improvement, the solvent evaporation process involves heating to remove most of the solvent, followed by drying the remaining solvent in a vacuum oven. The heating evaporation process is carried out at a temperature between 30°C and 80°C for 12 hours to 24 hours; the vacuum drying process is carried out at a temperature between 30°C and 80°C for 6 hours to 24 hours. This process ensures complete solvent evaporation, eliminating the adverse effects of residual solvent on battery performance.
[0045] As a further improvement, the hot pressing temperature is 30°C to 80°C.
[0046] A polymer solid electrolyte of lithium-ionized thermoplastic polyurethane elastomer prepared by the above method.
[0047] Example 1
[0048] (1) Preparation of novel sulfonated TPU
[0049] Weigh 15.00 g of ether-oxygen chain oligomer PTMG (polytetrahydrofuran) into a suitable three-necked flask. Under dry nitrogen protection, place the flask in a 45°C oil bath. Dissolve 4.29 g of diphenylmethane diisocyanate (MDI) in anhydrous CHCl3 and add it to the ether-oxygen chain oligomer with vigorous mechanical stirring. Heat to 60°C and react for 2 hours, then cool to obtain the prepolymer. Dissolve the chain extender polyethylene glycol in anhydrous organic solvent DMF and add it to the prepolymer. Gradually raise the temperature to 80°C and stir for about one day to obtain chain-extended polyurethane (TPU).
[0050] 10g of chain-extended polyurethane (TPU) was weighed and added to anhydrous DMF to prepare a solution. The solution was cooled to -5±1℃, and NaH was added and mixed thoroughly. When the temperature was raised to -6℃~5℃, a large number of bubbles were generated. The temperature was continued to rise until the reaction was complete and no more bubbles were generated. Then, PS (propane sulfonyl lactone) was weighed at -10℃, stirred and mixed, and reacted for 5 minutes. After that, the temperature was raised to room temperature and reacted for 2 hours. After cooling, excess NaH was quenched with 5ml of methanol quencher to obtain sodium-modified TPU polymer. Finally, Na ions were replaced with Li ions by ion exchange to obtain lithium-modified TPU material.
[0051] Based on different PS stoichiometric ratios, thermoplastic polyurethane elastomers with varying degrees of lithiation can be prepared, denoted as TPU(a%Li), TPU(b%Li), TPU(c%Li), and TPU(d%Li) according to their lithiation degree from low to high. Here, a, b, c, and d represent 33, 55, 66, and 100, respectively.
[0052] (2) Pretreatment of lithium-ionized TPU
[0053] The prepared lithium-ionized TPU was cast onto a polytetrafluoroethylene plate and placed in a vacuum oven at 65°C for one day to remove organic solvents. The completely dried TPU film was then freeze-dried and pulverized into fine powder for easy weighing.
[0054] (3) Preparation of polymer solid electrolyte based on lithium-ionized thermoplastic polyurethane elastomer (TPU)
[0055] First, weigh 160 mg of lithium-ionized TPU and 80 mg of LiTFSI into a sample vial according to the mass ratio. Dissolve the TPU in anhydrous DMF, an organic solvent, and then heat to 40 °C with stirring to obtain a TPU@LiTFSI solution. Pipette 50 μL of ionic liquid [BMIM]TFSI and slowly drop it into the TPU@LiTFSI solution. Stir at 40 °C for a period of time. Then, cast the solution onto a smooth PTFE (polytetrafluoroethylene) substrate and dry it on a heating stage for 24 h to remove most of the solvent. Next, place it in a vacuum oven and vacuum dry at 80 °C for 24 h. After static aging, peel off the film and hot-press it at 0.5 MPa and 80 °C for 2 min to prepare a polymer solid electrolyte film based on a novel lithium-ionized thermoplastic polyurethane elastomer (TPU). All the above operations are performed in a glove box or drying chamber.
[0056] The prepared polymer solid electrolyte was assembled into a steel sheet symmetric cell at room temperature, and its ionic conductivity was then measured at 30°C using a CHI660 instrument. The test voltage was 10 mV, and the frequency range was 1 MHz to 1 Hz. The test results are shown in Table 1 and... Figure 1 As shown.
[0057] TPU (0% Li) 30℃ 3.24078E-5 TPU(a%Li) 30℃ 3.88598E-4 TPU (b% Li) 30℃ 5.83848E-4 TPU (c% Li) 30℃ 3.4736E-4 TPU (d% Li) 30℃ 4.33331E-4
[0058] From Table 1 and Figure 1 As can be seen, compared to unlithiated TPU, lithiated TPU has more sites for direct coordination with Li and more charge carriers, namely lithium ions. Therefore, the sulfonation process increases the conductivity by an order of magnitude. The special branched structure of lithiated TPU endows it with good ionic conductivity, making it suitable for simple and efficient processing methods and applicable to polymer electrolytes in all-solid-state lithium-ion batteries.
[0059] Figure 2 These are the rate cycle test results of an all-solid-state lithium-ion battery assembled from TPU (c% Li) in the solid electrolyte prepared in Example 1. Figure 2 It can be seen that the lithium-modified TPU has better ionic conductivity due to the presence of more sites for direct coordination with Li and more charge carriers, i.e., lithium ions. Simultaneously, the unique branched structure of the lithium-modified TPU endows it with good mechanical properties, thus suppressing lithium dendrite growth. This results in a battery conductivity of 0.1 mA / cm² at room temperature after assembly into a full cell. 2 At a given current density, it exhibits a discharge specific capacity of 125 mAh / g and can cycle stably. This demonstrates that the polymer electrolyte prepared using this lithium-ion TPU as a single backbone has great potential for application in all-solid-state lithium-ion batteries.
[0060] Figure 3 This is a cycle stability diagram of a Li||Li symmetric battery based on a novel lithium-ionized TPU polymer solid electrolyte, as provided in Example 1 of this invention. Figure 3 As can be seen, the stability and compatibility of the interface between the polymer solid electrolyte and lithium metal can be explored by the fluctuation of the overpotential at the same current density in the curve. In the curve provided by the present invention, the overpotential is very stable at the same current density, indicating that the polymer solid electrolyte membrane prepared by the present invention has good compatibility with lithium and small interfacial side reactions.
[0061] This invention replaces the PEO backbone in traditional polymer electrolytes with an ionomer—lithiated thermoplastic polyurethane elastomer (TPU)—and introduces suitable small organic molecules as additives to obtain a solid electrolyte with both good ionic conductivity and excellent mechanical properties. This lithiated TPU polymer, with specific functional groups that interact with lithium ions, becomes an ionomer that can itself provide a lithium source. Its linear backbone also has more coordination sites than PEO, and its microphase-separated structure composed of hard and soft segments gives it both good mechanical properties and excellent ionic conductivity. The addition of a room-temperature ionic liquid facilitates lithium ion dissociation and enhances the mobility of polymer chains, thereby improving the conductivity of the polyelectrolyte. This invention uses a simple method of ionizing traditional TPU materials to transform them into ionomers, and then combining the ionomer with the ionized TPU polymer to prepare a polymer electrolyte with considerable performance. The preparation process is simple and efficient, eliminating the need for cumbersome electrospinning and electrolyte soaking steps, which is beneficial for large-scale commercial production. The polymer electrolyte prepared using this lithium-ion TPU as a single backbone exhibits no liquid leakage, making it a truly all-solid-state electrolyte. This provides new opportunities for the application of ionic polymers with sulfonate functional groups in all-solid-state lithium-ion batteries.
[0062] This invention employs a strategy of modifying block copolymer ionic polymers with room-temperature ionic liquids, resulting in solid electrolyte membranes that possess both good mechanical strength and high ionic conductivity. This imparts excellent interfacial compatibility between the solid electrolyte and the electrode, promoting stable ion deposition / stripping. Specific groups in the ionic liquid can compete with lithium ions for binding with sulfonic acid groups, promoting lithium ion dissociation and increasing the number of charge carriers, thereby improving the ionic conductivity of the solid electrolyte. Therefore, the prepared polymer solid electrolyte can achieve an ionic conductivity of up to 10 at room temperature. -4 S cm -1 It surpasses the ionic conductivity of most systems that use non-sulfonated TPU and additives as polymer electrolytes, making it suitable for application in all-solid-state lithium battery systems.
[0063] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a polymer solid electrolyte of a lithium-ionized thermoplastic polyurethane elastomer, characterized in that, Includes the following steps: S1, extend the polyurethane chain to obtain an extended polyurethane elastomer, then graft sulfonate groups onto the extended polyurethane elastomer through a sulfonation reaction and then lithiate it through ion exchange to obtain a lithium-ionized TPU, wherein the degree of lithiation of the lithium-ionized TPU is 30-100%; S2, Lithium-based TPU, a room-temperature ionic liquid as a functional additive, and a lithium salt are dissolved in an organic solvent, wherein the mass ratio of lithium-based TPU, functional additive, and lithium salt is 30-50wt%, 30-40wt%, and 10-30wt%, respectively. The mixture is heated and stirred for a period of time to form a composite solution. S3, the composite solution is poured onto a smooth substrate, the solvent evaporates, and the substrate is left to age for a period of time to form a film; S4, the film is peeled off, hot-pressed, and cut into pieces to form the polymer solid electrolyte of the lithium-ionized thermoplastic polyurethane elastomer; The steps for obtaining extended polyurethane elastomer by chain extension are as follows: a certain mass of ether-oxygen oligomer is weighed into a container, placed in an oil bath under an inert atmosphere, a certain amount of MDI is dissolved in anhydrous CHCl3, and added to the ether-oxygen oligomer with stirring. After heating and reacting for several hours, the mixture is cooled to obtain a prepolymer. The chain extender is dissolved in anhydrous organic solvent and added to the prepolymer. The temperature is gradually increased to about 70℃~100℃, and the mixture is stirred and reacted for a period of time to obtain the extended polyurethane elastomer. The room-temperature ionic liquid is one or more of [BMIM]TFSI, [EMIM]FSI, and [BMIM]OTF.
2. The preparation method according to claim 1, characterized in that, The ether-oxygen chain oligomers include one or more of polyethylene oxide, polyethylene glycol, and polytetrahydrofuran.
3. The preparation method according to claim 1, characterized in that, The chain extender includes one or more of polyethylene glycol, polybutylene glycol, and polyglycerol.
4. The preparation method according to claim 1, characterized in that, The hot pressing temperature is 30℃~80℃.
5. A polymer solid electrolyte of a lithium-ionized thermoplastic polyurethane elastomer prepared by the method of any one of claims 1 to 4.
Citation Information
Patent Citations
KR20210121884A